El apego y su relación con la autoestima en los niños y niñas de 3-4 años del centro de desarrollo infantil y escuela de educación inicial y básica ABC, de la ciudad de Riobamba, periodo 2013-2014 - Ortega Garzón, Andrea Paola (2014)
This thesis refers to: ADDICTION AND ITS RELATION TO SELF-ESTEEM IN CHILDREN 3-4 YEARS OF CHILDHOOD CENTER AND SCHOOL OF BASIC EDUCATION AND INITIAL DEVELOPMENT ABC, CITY Riobamba, 2013-2014. The general objective was: To establish the relationship between attachment and self-esteem of children of 3-4 years of the Child Development Center and School of Early Childhood Education and Basic ABC of Riobamba, 2013-2014. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Analytic, Synthetic, Descriptive and Statistical Model, the techniques used were: observation sheet to determine the type of attachment of children and Test application of Lewis R. Aiken to assess the self-esteem of children of 3-4 years of the child Development Center and School of Early Childhood Education and Basic ABC of Riobamba, 2013-2014. App of the observation sheet applied to children is concluded that: 70% of children show secure attachment, 13% show insecure-resistant attachment, 10% insecure - avoidant attachment, and 7 % state - insecure disorganized disoriented attachment. From the test results of Lewis R. Aiken concluded that: 63% of children achieved a level of self-esteem development Highly Satisfactory, Satisfactory 32%, and 5% Unsatisfactory. It is important to the development of self-esteem because the child will develop successfully.